PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 21 PADANG - -, Yuhelmi - (STKIP PGRI Sumbar, 2014)
This research beginning be fact in SMPN 21 Padang that lesson is still going on one direction until make the process of lesson less gratify. One of the way that can be muddling through the problem is by applying of learning active strategy of learning tournament type. A type of this research is the research of pra-experiment with the program of one shot case study. The instrument of research is quiz and final test in essay form that contain of indicator comprehension concept. Form of the test can be used is amaunt of 7 question list with reabilitas test r11= 0,77. Based on the result of the analysis quiz of data and final test. The avarage of quiz I is result 79,31,quiz II is 84,29, quiz III is 85,89, and quiz IV is 86,67, the result of the hypothesis test acquire t=5,238 and ttable=1,960. This matter means the hypothesis to this research is received.